Analisis Implementasi Program Penurunan Stunting dalam Dokumen Perencanaan Pembangunan Daerah Kota Serang - Elisabet Claudya Septiani Silaban; Laeli Nur Khanifah; Salwa Zahira; Aisyah Machiqa Ilmi; Brigita Putri Marito (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study was designed to systematically analyze how stunting reduction programs in Serang are planned and implemented through regional development planning documents. The findings indicate that the implementation of stunting reduction programs in Serang City has been integrated into regional development planning documents, such as the Regional Medium-Term Development Plan (RPJMD), Regional Government Work Plan (RKPD), Strategic Plans (Renstra), and Annual Work Plans (Renja) of regional government agencies. This integration demonstrates that stunting has been positioned as a regional development agenda rather than merely a health sector issue. However, its implementation continues to face challenges related to inter-agency coordination, data quality, human resource capacity, budget effectiveness, and community participation. Therefore, the success of stunting reduction programs in Serang City depends not only on the availability of planning documents but also on the consistency of implementation, cross-sectoral coordination, and the local government's ability to adapt programs to community needs.